The “rebirth” of traditional musical instrument: An interactive installation based on augmented reality and somatosensory technology to empower the exhibition of chimes - Guo, Wenchen; Huang, Yiyuan; Chen, Zhirui; Zhang, Zixun; Sun, Guoyu; Zeng, Qingxiang; Li, Xiao (Computer animation and virtual worlds, 2023)
Tangible cultural heritage is rich in historical, artistic and scientific value, but due to its own characteristics and the constraints of museum displays, the key issue facing us today is how to utilize and activate cultural heritage to enhance the experience and learning interest of the audience. Focusing on the Chinese cultural treasure, the chimes, this article innovatively proposes an interaction system based on digital augmented projection and somatosensory technology to empower the aesthetic expression and knowledge dissemination of chimes. On this basis, a series of evaluations were carried out and the results showed that the system effectively provides a satisfying, personalized and fun way for users to interact with chimes and learn the traditional culture, successfully bringing this ancient instrument back to life. Moreover, this article shares in detail the research, design and development process, which provides inspiration and examples for other museums to present their tangible cultural heritage through mixed reality and interactive technology. This article innovatively proposes an interaction system named Encounter with Chimes which based on digital augmented projection and somatosensory technology to empower the aesthetic expression and knowledge dissemination of chimes. Moreover, a series of evaluations were carried out and the results showed that the system effectively provides a satisfying, personalized and fun way for users to interact with chimes and learn the traditional culture, successfully bringing this ancient instrument back to life.